Interactive online modules for dental education: a practical example of Gagne’s nine events of instruction - Lin, Galvin Sim Siang; Foong, Chan Choong; Abd Aziz, Yang Faridah (Penerbit USM, 2024)
Effective and engaging learning experiences are crucial in dental education, especially in the field of dental materials science, as previous approaches were largely through didactic teaching. Interactive online modules have emerged as valuable supplemental tools to enhance dental education. It offers interactive elements, promotes active learning, and provides an immersive, self-paced learning environment. This article highlights the use of Gagne’s Nine Events of Instruction as a practical framework to design and implement interactive online modules in the dental materials science curriculum. Gagne’s model provides a structured approach to instructional design, improving students’ engagement and their learning process. The development of interactive online modules follows Gagne’s model, including gaining attention, informing students of objectives, stimulating the recall of prior knowledge, presenting new material, providing guidance, eliciting performance, providing feedback, assessing performance, and enhancing retention and transfer. Students’ perceptions and feedback can be evaluated at the end of the online modules. In short, this article provides a systematic approach to the design and implementation of interactive online modules, ultimately improving the educational outcomes for dental and other health profession students.